Physical in Tension Reproductive System Reactivity - Fazliddinovna, Boboqandova Mehriniso (American Journal of Bioscience and Clinical Integrity, 2025)
Physical tension organism various in systems, that including reproductive also noticeable in the system to changes take comes. Physical of tension reproductive to the system how impact to show, its physiological mechanisms and health for importance about word goes. Physical activity done increase during organism many physiological to changes face comes. Among these heart and blood vein system, respiratory to take system, muscle system and There are others. Also, reproductive the system is also physical to strain in response changes. Physical exercises and tension organism hormones working in the release important role plays and reproductive of the system function directly impact does. Physical exercises men’s sperm quality and sexual hormone, especially testosterone to the level noticeable impact to show This effect is possible. physical activity type, duration and to the intensity related.